Plotting Poetry 7: Metres of Humour. Conference report - Neža Kočnik; Chris Mustazza; Benjamin Nagy; Yelena Sesselja Helgadóttir (Studia Metrica et Poetica)
Plotting Poetry 7: Metres of Humour. Conference report